Pressure effects on iron-based superconductor families: Superconductivity, flux pinning and vortex dynamics. (July 2021) - Sang, L.N.; Li, Z.; Yang, G.S.; Yue, Z.J.; Liu, J.X.; Cai, C.B.; Wu, T.; Dou, S.X.; Ma, Y.W.; Wang, X.L.
Abstract: Since the discovery of iron-based superconductors, a new chapter has been opened in the history of the development of high temperature superconductivity. In the past decade, there have been remarkable achievements in the theory, experiments, and applications of iron-based superconductors, and our understanding of the mechanism of superconductivity has been deeply enriched. Here, we review the research progress on high-pressure studies on the superconductivity, flux pinning, and vortex dynamics of iron-based superconductor families. The topics include pressure-induced superconductivity, raising the superconducting transition temperature, pressure-induced elimination and re-emergence of superconductivity, the effects of phase separation on superconductivity, increasing the critical current density, significantly suppressing vortex creep, and reducing the size of the flux bundles. Graphical abstract: Image 1 Highlights: Here, it is the first review that the high-pressure studies on flux pinning and magnetic relaxation. This review summarizes the recent research progress on the pressure effects and provides a comprehensive review for IBSC.